BS EN 61753-022-13. Fibre optic interconnecting devices and passive components. Performance standard. Part 022-13. Fibre optic connectors terminated on multimode fibre for category OP+ HD. Extended outdoor protected environment with additional heat dissipation (12th March 2021) - British Standards Institution,
No abstract available